1984
DOI: 10.1111/j.1365-3032.1984.tb00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of immature queen honeybees (Apis mellifera) on queen rearing and foraging

Abstract: ABSTRACT. Providing queenless colonies with five queen cells containing larvae or pupae diminished the number of queen cells and queen cell cups subsequently produced, but not as effectively as the provision of a mated laying queen. Immature queens were more effective than the mature queens in stimulating pollen collection, but were less effective in stimulating nectar collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Because queen larvae and pupae are attended by as many workers as attend virgin queens, they probably also produce attractive pheromones although they contain only traces of 9-ODA (Butler & Paton, 1962;Boch, 1979). Queen larvae and pupae inhibit queen rearing and encourage foraging, but less effectively than a mated queen (Free et al, 1984). Workers frequently and readily contact queen larvae and may easily obtain pheromone from them.…”
Section: Part Of Queen's Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Because queen larvae and pupae are attended by as many workers as attend virgin queens, they probably also produce attractive pheromones although they contain only traces of 9-ODA (Butler & Paton, 1962;Boch, 1979). Queen larvae and pupae inhibit queen rearing and encourage foraging, but less effectively than a mated queen (Free et al, 1984). Workers frequently and readily contact queen larvae and may easily obtain pheromone from them.…”
Section: Part Of Queen's Bodymentioning
confidence: 99%
“…It seems that workers in the court obtain queen pheromone on their antennae and distribute it in the colony by antenna1 contact with other workers (Free, 1978;Seeley, 1979;Ferguson & Free, 1980;Juska el nl., 1981). Immature queens also produce pheromones (Boch, 1979;Free et al, 1984) which are probably distributed in a similar way (Free & Ferguson, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The technique was similar to that used previously (Free et a/., 1984). There were three experiments; the weather was hot, dry and sunny throughout each.…”
Section: Methodsmentioning
confidence: 99%
“…and rear their occupants as queens. Recent experiments (Free et al, 1984) demonstrated that pheromone produced from queen cells, containing larvae or pupae, diminishes production of additional queen cells but not as effectively as pheromone from a mated laying queen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation